Assessment of patients' understanding of inflammatory bowel diseases: Development and validation of a questionnaire. Issue 1 (23rd December 2021) - Ostromohov, Gaiana; Fibelman, Morin; Hirsch, Ayal; Ron, Yulia; Cohen, Nathaniel Aviv; Kariv, Revital; Deutsch, Liat; Kornblum, Jasmine; Anbar, Ronit; Maharshak, Nitsan; Fliss‐Isakov, Naomi
Abstract: Background: Educating patients regarding thier inflammatory bowel disease (IBD) is important for their empowerment and disease management. We aimed to develop a questionnaire to evaluate patient understanding and knowledge of IBD. Methods: We have developed the Understanding IBD Questionnaires (U‐IBDQ), consisting of multiple‐choice questions in two versions [for Crohn's disease (CD) and ulcerative colitis (UC)]. The questionnaires were tested for content and face validity, readability, responsiveness and reliability. Convergent validity was assessed by correlating the U‐IBDQ score with physician's subjective assessment scores. Discriminant validity was assessed by comparison to healthy controls (HC), patients with chronic gastrointestinal (GI) conditions other than IBD, and to GI nurses. Multivariate analysis was performed to determine factors associated with a high level of disease understanding. Results: The study population consisted of IBD patients ( n  = 106), HC ( n  = 35), chronic GI disease patients ( n  = 38) and GI nurses ( n  = 19). Mean U‐IBDQ score among IBD patients was 56.5 ± 21.9, similar for CD and UC patients ( P  = 0.941), but significantly higher than that of HC and chronic GI disease patients and lower than that of GI nurses ( P  < 0.001), supporting its discriminant validity. The U‐IBDQ score correlated with physician's subjective score ( r  = 0.747, P  < 0.001) and was found to be reliable (intra‐class correlation coefficient = 0.867 P  < 0.001). Independent factors associated with high U‐IBDQ scores included academic education (OR = 1.21, 95% CI 1.10–1.33, P  < 0.001), biologic therapy experience (OR = 1.24, 95% CI 1.01–1.53, P  = 0.046), and IBD diagnosis at <21 years of age (OR = 2.97, 95% CI 1.05–8.87, P  = 0.050). Conclusions: The U‐IBDQ is a validated, reliable and short, self‐reported questionnaire that can be used for assessing understanding of disease pathophysiology and treatment by IBD patients. Key summary: Established knowledge on this subject Inflammatory bowel diseases (IBD) patients' beliefs and knowledge regarding their disease may affect disease management, quality of life and disease‐related psychological health. Therapy‐related disinformation is associated with low adherence to treatment. A standardized and validated tool for assessment of IBD patients' knowledge and understanding of their disease is lacking. Significant findings of this study We developed and meticulously validated the understanding of IBD questionnaire, a short questionnaire aimed at measuring understanding of disease pathophysiology and treatment of IBD. Inflammatory bowel diseases‐related knowledge was associated with education level and with younger age at IBD diagnosis.